Conservation of proteins involved in oocyst wall formation in Eimeria maxima, Eimeria tenella and Eimeria acervulina. - Belli, S; Ferguson, D; Katrib, M; Slapetova, I; Mai, K; Slapeta, J; Flowers, SA; Miska, K; Tomley, F; Shirley, M; Wallach, MG; Smith, N (2009)
Vaccination with proteins from gametocytes of Eimeria maxima protects chickens, via transfer of maternal antibodies, against infection with several species of Eimeria. Antibodies to E. maxima gametocyte proteins recognise proteins in the wall forming bodies of macrogametocytes and oocyst walls of E. maxima, Eimeria tenella and Eimeria acervulina. Homologous genes for two major gametocyte proteins - GAM56 and GAM82 - were found in E. maxima, E. tenella and E. acervulina. Alignment of the predicted protein sequences of these genes reveals that, as well as sharing regions of tyrosine richness, strong homology exists in their amino-terminal regions, where protective antibodies bind. This study confirms the conservation of the roles of GAM56 and GAM82 in oocyst wall formation and shows that antibodies to gametocyte antigens of E. maxima cross-react with homologous proteins in other species, helping to explain cross-species maternal immunity.